Pengaruh Karbon Aktif Ampas Tebu (Adsorben) terhadap Air Asam Tambang untuk Mengurangi Kadar Fe, Mn, dan TSS pada Sump PT Alreksa Bara Mitra - Brilliant Mercy Geometri; Shalaho Dina Devy; Lucia Litha Respati; Harjuni Hasan; Rety Winonazada (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
Acid mine drainage (AMD) is one of the major environmental problems arising from coal mining activities. AMD is formed through the oxidation of sulfide minerals, resulting in acidic water with high concentrations of dissolved heavy metals. This condition is characterized by elevated levels of Fe, Mn, and total suspended solids (TSS), which, if left untreated, can pollute nearby water bodies, damage aquatic ecosystems, and pose risks to human health. Therefore, effective, eco-friendly, and low-cost treatment methods are needed to minimize the negative impacts of AMD. This study aims to investigate the effect of activated carbon derived from sugarcane bagasse as an adsorbent for reducing Fe, Mn, and TSS levels in AMD at the sump of PT Alreksa Bara Mitra. The selection of sugarcane bagasse is based on its abundance as an agro-industrial waste and its high lignocellulosic content, making it a potential raw material for activated carbon. The research involved the preparation of activated carbon through carbonization and activation processes, followed by its application to AMD samples with variations in adsorbent dosage and contact time. Laboratory analyses were conducted to measure the concentrations of Fe, Mn, and TSS before and after treatment. The results showed that sugarcane bagasse-based activated carbon significantly reduced Fe, Mn, and TSS concentrations. The highest removal efficiencies were achieved under optimum conditions, reaching 93.14% for Fe, 95.05% for Mn, and 85.04% for TSS. These findings demonstrate that activated carbon from sugarcane bagasse has a strong adsorption capacity for dissolved metals and suspended solids in AMD. In conclusion, sugarcane bagasse-derived activated carbon has potential as an environmentally friendly and cost-effective alternative for AMD treatment, while simultaneously providing added value to agro-industrial waste. This research is expected to serve as a reference for the development of more sustainable mine wastewater treatment methods.